2005
DOI: 10.1007/s10750-004-4970-4
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomy, morphology and speciation of the Semicytherura henryhowei group (Crustacea, Ostracoda)

Abstract: The genus Semicytherura belongs to the family Cytheruridae, and was distinguished from Cytherura on the basis of carapace features. Species of Semicytherura from Japan and adjacent seas can be divided into two groups. One is represented by Semicytherura miurensis Hanai, 1957, characterized by a thin, oval carapace covered with fine reticulation. The other is represented by Semicytherura henryhowei Hanai & Ikeya, 1977, characterized by a thick sub-rectangular carapace in lateral view. Semicytherura henryhowei, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 17 publications
0
42
0
Order By: Relevance
“…Yamada et al (2005) and Yamada and Tsukagoshi (2010) has reported 4 benthic Semicytherura species. Semicytherura sasameyuki Yamada et al, 2005 was collected from the sediment samples of Maizuru Bay, and the other three species, S. slipperi Yamada et al, 2005, S. maxima Yamada and Tsukagoshi, 2010, and S. ikeyai Yamada and Tsukagoshi, 2010 were collected from the dredged samples of Akkeshi Bay. Based on the kind of the samples, it is possible that these species are infaunal.…”
Section: Discussionmentioning
confidence: 99%
“…Yamada et al (2005) and Yamada and Tsukagoshi (2010) has reported 4 benthic Semicytherura species. Semicytherura sasameyuki Yamada et al, 2005 was collected from the sediment samples of Maizuru Bay, and the other three species, S. slipperi Yamada et al, 2005, S. maxima Yamada and Tsukagoshi, 2010, and S. ikeyai Yamada and Tsukagoshi, 2010 were collected from the dredged samples of Akkeshi Bay. Based on the kind of the samples, it is possible that these species are infaunal.…”
Section: Discussionmentioning
confidence: 99%
“…The carapace of S. sagittijbrnzts (O.34 mm in length and O.15mm in height on average) is smaller than those of other epibenthic Semiaytherura (O.44mm in lengtli and e.23mm in height on average) and is comparable with those of some large interstitial ostracods (e.g., Microtoxo- tijbrntis. Data compiled from Sars (1866), Hanai (1957), Ishizaki (1966Ishizaki ( , 1981, Hazel and Valentine (1969), Schorriikev (1975), , Hanai et al, (1977), ), Frydl (1982, Yajima (1982), Tabuki (1986), Nohara (1987), Hiruta (1989Hiruta ( , 1991, lkeya et al <1992), Irizuki et al (2004), Yamada et al (2005), Hir'uta et al, (2007)…”
Section: Discussionmentioning
confidence: 99%
“…In any case, in many taxa the morphology of the copulatory organs is considered as a helpful tool in the identification of different species and in distinguishing sibling taxa, since even closely related species with similar morphology have strikingly different genitalia (Curini‐Galletti and Puccinelli 1998; Šimková et al . 2002; Yamada et al . 2005; Pastorino and Cohen 2006).…”
Section: Discussionmentioning
confidence: 99%